2020
DOI: 10.35848/1347-4065/ab7add
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Al2O3-GaN capacitors with an ultraviolet/ozone plasma-treated interface

Abstract: In this study, interface quality of p-type GaN metal-oxide-semiconductor capacitors (n-MOSCAPs) improved with the interface oxide layer (Ga 2 O x ) formed by ultraviolet/ozone (UV/O 3 ) treatment. X-ray photoelectron spectroscopy, transmission electron microscopy, and X-ray dispersive spectroscopy were employed to investigate the Ga 2 O x interface layer which reduced trapped charge density (Q ot ) and interface trap density (D it ) of n-MOSCAPs. The thickness of the Ga 2 O x layer was found to be ∼1 nm. From … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…Table 1 summarizes the reported D it values at the Al 2 O 3 /p-GaN interface [22,[29][30][31]. The D it in this work are comparable to the reported ones at the Al 2 O 3 /p-GaN interface [22,[29][30][31], and obviously higher than those at the Al 2 O 3 /n-GaN interface [32,33].…”
Section: Analysis Of the Interface Traps By The Ac Conductance Techniquesupporting
confidence: 81%
“…Table 1 summarizes the reported D it values at the Al 2 O 3 /p-GaN interface [22,[29][30][31]. The D it in this work are comparable to the reported ones at the Al 2 O 3 /p-GaN interface [22,[29][30][31], and obviously higher than those at the Al 2 O 3 /n-GaN interface [32,33].…”
Section: Analysis Of the Interface Traps By The Ac Conductance Techniquesupporting
confidence: 81%
“…Higher threshold voltages were previously reported in the literature with decreasing GaO x interfacial layer thickness for ALD-Al 2 O 3 /n-GaN MOS capacitors and MOCVD-Al 2 O 3 MOS-HEMTs, attributed to ionized donor levels at the Al 2 O 3 /GaO x interface . On the other hand, Kim et al reported good interfacial properties using UV/O 3 treatment, showing that an ultrathin good-quality Ga-oxide layer can be beneficial . Therefore, we can expect a higher threshold voltage for an MOSc-HEMT by either further decreasing Ga oxidation or by controlling the properties of the Ga-oxide interfacial layer .…”
Section: Resultsmentioning
confidence: 60%
“…31 On the other hand, Kim et al reported good interfacial properties using UV/O 3 treatment, showing that an ultrathin good-quality Ga-oxide layer can be beneficial. 32 Therefore, we can expect a higher threshold voltage for an MOSc-HEMT by either further decreasing Ga oxidation or by controlling the properties of the Ga-oxide interfacial layer. 33 Since the Ga oxidation is higher for etched samples than as-epi samples (see Figure 4), we can conclude that the etching-induced damage has a detrimental impact on the threshold voltage.…”
Section: Resultsmentioning
confidence: 79%
“…On the other hand, as for the forward sweeps of the low and medium samples, both the maximum capacitance and the gate voltage showed a discrepancy between the experimental and ideal values that became pronounced depending on the doping conditions, suggesting a change in the density and energy distribution of hole traps near the interface. On the basis of these findings and previous reports, [19][20][21][22][23][24][25][26] it can be concluded that rather than the UHPA process, 27) the concentration of Mg atoms and/or the Fermi level of the p-GaN substrate play a decisive role in the passivation of hole traps.…”
supporting
confidence: 64%
“…17,18) In contrast, there are few reports on p-type GaN MOS capacitors that had well-behaved capacitance-voltage (C-V ) characteristics. [19][20][21][22][23][24] Because of the significant number of hole traps located near the oxide/GaN interfaces, a large C-V hysteresis is usually observed for p-type MOS capacitors. 25) Even worse, the surface potential of GaN is pinned and an ideal amount of hole accumulation at the MOS interface hardly occurs regardless of the gate dielectric materials used.…”
mentioning
confidence: 99%